ChemInform Abstract: Metallic Borides, La2Re3B7 and La3Re2B5, Featuring Extensive Boron—Boron Bonding. Issue 17 (April 2016) - Bugaris, Daniel E.; Malliakas, Christos D.; Chung, Duck Young; Kanatzidis, Mercouri G.
Abstract: Single crystals of La2 Re3 B7 (I) and La3 Re2 B5 (II) are grown from mixtures containing the elements in the La:Re:B molar ratio of 1:3:5 covered by a La/Ni eutectic (compound (I)) or 1:2:1 with 1 equiv.